Polyimide mesh-based sample holder with irregular crystal mounting holes for fixed-target serial crystallography - Ki Hyun Nam (Nature Portfolio, 2021)
Abstract The serial crystallography (SX) technique enables the determination of the room-temperature structure of a macromolecule while causing minimal radiation damage, as well as the visualization of the molecular dynamics by time-resolved studies. The fixed-target (FT) scanning approach is one method for SX sample delivery that minimizes sample consumption and minimizes physical damage to crystals during data collection. Settling of the crystals on the sample holder in random orientation is important for complete three dimensional data collection. To increase the random orientation of crystals on the sample holder, we developed a polyimide mesh-based sample holder with irregular crystal mounting holes for FT-SX. The polyimide mesh was fabricated using a picosecond laser. Each hole in the polyimide mesh has irregularly shaped holes because of laser thermal damage, which may cause more crystals to settle at random orientations compared to regular shaped sample holders. A crystal sample was spread onto a polyimide-mesh, and a polyimide film was added to both sides to prevent dehydration. Using this sample holder, FT-SX was performed at synchrotron and determined the room-temperature lysozyme structure at 1.65 Å. The polyimide mesh with irregularly shaped holes will allow for expanded applications in sample delivery for FT-SX experiments.